2016
DOI: 10.1016/j.sapharm.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring supervision and reconfiguration of skill mix in community pharmacy: Classification of perceived safety and risk

Abstract: This paper presents novel empirical evidence informing the categorization of pharmacy activities into 'safe,' 'borderline' or 'unsafe.' 'Borderline' activities will deserve particular attention, especially where they are part of processes, e.g. dispensing. This categorization could help inform reconfiguration of skill mix in community pharmacy and thus make an important contribution to the rebalancing medicines legislation agenda and pharmacist supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Denmark, the Netherlands) pharmacy technicians routinely undertake dispensing without pharmacist supervision, in the UK and US pharmacists are required to either undertake or supervise different parts of the process. Some research exists which supports the expansion of the roles of pharmacy technicians and other support staff in community pharmacy[ 24 , 25 ] which would help free up pharmacists’ time for clinical roles.…”
Section: Discussionmentioning
confidence: 99%
“…Denmark, the Netherlands) pharmacy technicians routinely undertake dispensing without pharmacist supervision, in the UK and US pharmacists are required to either undertake or supervise different parts of the process. Some research exists which supports the expansion of the roles of pharmacy technicians and other support staff in community pharmacy[ 24 , 25 ] which would help free up pharmacists’ time for clinical roles.…”
Section: Discussionmentioning
confidence: 99%
“…52 Within the UK, although task delegation is reported to be widely employed within community pharmacies and support staff are considered competent to absorb further roles, barriers to task delegation exist and include concerns over accountability, with mixed views about the reconfiguration of the skill mix within community pharmacies. 53,54 As participants within this study reported positively that the process map could encourage staff involvement, the generic process map could be disseminated to pharmacies as an operational tool to facilitate implementation by promoting whole-team engagement and task delegation. The use of process maps in community pharmacy has previously been suggested to improve efficiency, identify support staff roles and ensure higher skilled staff perform tasks only themselves can do, 47 echoing some of the participants comments within this study.…”
Section: Discussionmentioning
confidence: 93%
“…There is evidence from pharmacy technicians and preregistration pharmacists that training differs between the two main sectors, with hospital trainees working in larger, multiprofessional teams with dedicated study time. Furthermore, qualified hospital staff work in more advanced roles . Whilst there is some evidence that the nonregulated pharmacy assistant workforce is historically transient in nature, with a lack of robust and sustainable education pathways and poor career progression, relatively little is known regarding their practice or training .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, qualified hospital staff work in more advanced roles. [1,10,13,14] Whilst there is some evidence that the nonregulated pharmacy assistant workforce is historically transient in nature, with a lack of robust and sustainable education pathways and poor career progression, [15] relatively little is known regarding their practice or training. [3] Nevertheless, it is important that pharmacy assistants enable the release of pharmacists and pharmacy technicians to deliver high-quality near-patient services, to enable delivery of the government vision for health care.…”
Section: Introductionmentioning
confidence: 99%